Development of Educational Tourism Areas in Naga Sopa Village, Bandar Huluan District, Simalungun Regency - Sinulingga, Samerdanta; Susilo, Hariadi; Lubis, Haris Sutan (Talenta Publisher, 2021)
The choice of the location of Naga Sopa Village as a place of service cannot be separated from the sustainability of the activities that have been held by the University of North Sumatra in the field of Student Community Service in the area of Simalungun Regency before. Based on the information that has been inventoried, this village has 4 main problems, such as: 1) tourism managers do not have the expertise and skills in making tourism activities; 2) Weak tourism awareness from both sides, both from tourism managers and tourists; 3) The community is still weak in the management of tourist destinations, even tourists do not know that this tourist location is a legacy of Dutch colonialism; 4) The low flow of tourist visits to these locations has an impact on the low public interest in managing these tourist attractions. Through this educational tour, non-formal education about knowledge can be applied to tour managers and tourists visiting a tourist attraction. Educational tours can increase and strengthen Tourism awareness groups to support the governance of the attraction of Swembat baths as a tourist icon. Tourism promotion media through tourism film training for the Swembat Naga Sopa tourism committee, Bandar Huluan District, is also needed to increase tourist visits to Swembat after the service is carried out so that the impact of service can be applied. This technically helps them to compete in the tourism sector.